Democratisation via elections in an African 'narco state'? The case of Guinea-Bissau - Dirk Kohnert (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, 2010)
Recent development cooperation with Guinea-Bissau, focusing on good governance, statebuilding and conflict prevention, did not contribute to democratization nor to the stabilization of volatile political, military and economic structures. The portrayal of Guinea- Bissau as a failed “narco-state”, as well as Western aid meant to stabilize this state, are both based on dubious concepts. Certainly, the impact of drug trafficking could endanger democratization and state-building if continued unchecked. However, the most pressing need is not state-building facilitated by external aid that is poorly rooted in the social and political fabric of the country. Rather, it is grassroots nation-building that is a pre-condition for the creation of viable state institutions. – – La démocratisation par le biais des élections dans un «narco-État» de l'Afrique? Le cas de la Guinée-Bissau: La coopération de développement récente avec la Guinée-Bissau, en se concentrant sur les élections, la consolidation de la bonne gouvernance et l'état de prévention des conflits, ni contribué à la démocratisation, ni à la stabilisation des structures politiques, militaires et économiques volatiles du pays. Tant la représentation de la Guinée-Bissau comme un échec «narco-État» ainsi que l'aide occidentale destinée à stabiliser cet état grâce à l'appui des élections multipartites sont basées sur des concepts et des hypothèses douteuses. Certes, l'impact du trafic de drogue pourrait mettre en danger la démocratisation et le renforcement de l'État si il se poursuit sans frein. Cependant, le besoin le plus urgent n'est pas le renforcement de l'État, mal ancré dans le tissu social et politique du pays, facilitée par l'aide extérieure, mais la construction d'une nation par le bas comme une condition préalable à la création d'institutions étatiques viables.
Additional information: Author's Version
Keywords: N4; Z1; Z13; O17; E26; H76; D72; K14; 330; Democratization; narco states; Guinea-Bissau; West Africa; good governance; fragile states; Demokratisierung; Politisches System; Rechtsstaat; Guinea-Bissau; Drogenwirtschaft; Good Governance; Fragiler Staat; Westafrika